Multiple cutaneous reticulohistiocytomas in a patient with rheumatoid arthritis - Vieira, R (2004)
A 64-year-old woman with a long-standing peripheral symmetric polyarthritis with positive rheumatoid serology was evaluated for multiple asymptotic papulonodules of fingers, mentum, lower lip, ears, and eyelids. Histopathologic examination showed a dermal infiltrate composed of histiocytes, multinucleate giant cells with ground-glass cytoplasm, and lymphocytes, suggestive of reticulohistiocytoma. The possibilities of multicentric reticulohistiocytosis with positive rheumatoid serology or coexistence of multiple cutaneous reticulohistiocytomas and rheumatoid arthritis are discussed.